IDENTIFIKASI POTENSI PARIWISATA BUDAYA DI KAMPUNG ADAT PRAI IJING, KECAMATAN KOTA WAIKABUBAK, SUMBA BARAT NTT - Fatrisia Yulianie; Fransiska FIla Hidayana (Jurnal Kajian dan Terapan Pariwisata, 2020)
This article is about a cultural tourism in the Prai Ijing Traditional Village, Waikabubak City District, West Sumba, East Nusa Tenggara. The aim of this article is to discuss the tourism development and identify the potential of cultural tourism in the Prai Ijing Traditional Village, Waikabubak City District, West Sumba, East Nusa Tenggara. The data were collected by observation, interviews, and documentation. The sampling techniques were purposive sampling. The data were analyzed using descriptive qualitative analysis to give an overview of the identity of the potential of cultural tourism in the Prai Ijing Traditional Village. The results of the analysis show that The Traditional Village of Prai Ijing is one of the potential tourist destinations with a megalithic grave bed and traditional house inside having a unique culture, a strategic location, and having been visited by tourists. The tourism development is managed by Bumdes Iyya Tekki and the entire village community. The development is able to provide additional income for th local community. There are efforts to improve the quality of human resources through skill training and english class. There are tourism components in supporting tourism development, namely attractions, accessibility, amenities, and the existence of a management institution (ancillary). As input for further development, it is necessary to maintain the cultural preservation and local wisdom, improve the service quality, the diversity of attractions and tourist activities in Prai Ijing Traditional Village